The estimation of evapotranspiration in kuantan using different methods - Nur Ain, Mohammah Fuzia (2017)
Evapotranspiration (ET) is a term represents the combination of two processes water cycle whereby water is lost to the atmosphere from the soil and water bodies’ meanwhile transpiration from vegetation or plant. The importance of ET due to the climate change which mainly expected to affect the air temperature, precipitation intensity and distribution. The objective of the study is to estimate and analyse the value of evapotranspiration by using Penman-Monteith (PM), Blaney-Criddle (BC) and Turc method in Kuantan, Pahang. In this study, the evapotranspiration value can obtain based on a program that we develop for the period 15 years from 2001 until 2015. Evapotranspiration can be effect the water level whether high or low, soil moisture, water supply, irrigation and agricultural. However, there are various types of method can be used for the calculation of ET. All ET methods present different structural complexity and data requirements. The methods was compared the values of appropriate methods with the exact ET values by develop a calculation program for ET calculation. Based on the ET value for the smallest value during month December to February. The most suitable method for ET value based on this study is Turc method and followed by Penman-Monteith due to the radiation-based parameter.